(untitled) (KASBIT Business Journal, 2022)
This study looked at how innovative work behavior is affected by procedural and distributive justice. In addition, the study looked at how intrapreneurial personality affects each aspect of justice and innovative work behavior. This study evaluated the moderating role of intrapreneurial personality in the connection between the component of justice and innovative work behavior in the Pakistani services industry using a questionnaire survey method. To test the hypothesis and investigate the moderating role, SPSS has utilized hierarchical regression. The findings demonstrated a significant correlation between innovative work behavior and distributive and procedural justice. In addition, their relationship is significantly and positively altered by the intrapreneurial personality. Later, the study concludes by discussing implications and present future directions.